Menilik Perbandingan Pembelajaran Qur’an Dan Hadits Di Indonesia dan Malaysia: Sebuah Studi Literatur - Tutik Nurhidayati (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2023)
Studying the Al-Qur'an Hadith aims to make students like to read the Al-Qur'an and Hadith correctly, and learn, understand, believe in their truth, and practice the teachings contained therein as instructions and guidelines in all aspects of life. Thus learning Al-Qur'an Hadith has a more special function compared to others in terms of learning Al-Qur'an. The purpose of this short article is to describe a comparison of how Al-Qur'an and Hadith are studied in two countries, namely Indonesia and Malaysia. This study used a qualitative method with a library research approach or literature study. The results of this study indicate that there are some similarities and differences in the practice or implementation of learning.